Upaya Preventif terhadap Kejadian Cacingan pada Anak Sekolah di SDN Bayem 01, Kasembon, Kabupaten Malang - Aloysia Ispriantari; Musthika Wida Mashitah (Universitas 45 Surabaya, 2025)
Deworming is one of the infectious diseases that is still commonly found in elementary school children in Indonesia, especially in rural areas with inadequate sanitation conditions. SDN Bayem 01, located in Kasembon Village, Kasembon District, is an area where the majority of the population works as farmers. The large open land areas used by children as playgrounds increase the risk of deworming transmission through contaminated soil. This community service activity aims to enhance students' knowledge and awareness regarding deworming prevention through education and promoting clean and healthy living behavior. The activity was conducted in two sessions: education on deworming diseases and promotion of Handwashing with Soap (CTPS) using educational videos and interactive songs to make it easier for children to understand. The evaluation results showed an increase in students' understanding of the causes, transmission, and prevention efforts of deworming. Additionally, students were able to correctly demonstrate the six steps of CTPS and enthusiastically participated in the activity. It is hoped that this activity will foster sustainable collaboration between the school, community health center, and parents in monitoring and providing regular education to reduce the incidence of deworming among elementary school children.